(untitled) (Theological Kronos, 2024)
This paper seeks to contribute to ecumenical discussions on the sacrament of Eucharist from a pneumatological approach. Starting from the theology of John Wesley and Thomas Aquinas, the author argues that Communion is a sacrament that communicates divine love through the Incarnate Christ by the power of the Spirit. As a result, the Eucharist shapes the identity and vocation of the church as the Body of Christ in the world. Further, in Communion, the Spirit leads the local Christian assemblies - as localized Bodies of Christ - toward a catholicism of encounter and inclusion rather than fragmentation and competition. The paper concludes that the Lord’s Table nourished a spirituality that seeks to embody Christ’s love for the suffering and marginalized neighbor. The author invites further reflection on the Eucharist as a liturgical practice that, rather than dividing, motivates ecumenical work.